The utilization of Solidity programming language in blockchain - Stanišić, Sava S.; Stojanović, Hristina N.; Đorđević, Igor Lj. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: This work provides a comprehensive overview of blockchain technology, elucidating its foundational principles and how it ensures transparency, immutability, and decentralization. The integration of Solidity with blockchain is explored through theoretical approach.Methods: This work meticulously dissects blockchain principles, elucidating transparency, immutability, and decentralization, while exploring Solidity integration in a theoretical framework, ensuring a comprehensive understanding of their intricate relationship and contributing to a broader comprehension of modern distributed ledger technology.Results: The resulting product of this paper will be getting useful knowledge about the technology that practically shapes the world.Conclusion: In conclusion, the adoption of Solidity as a programming language in blockchain technology has proven to be pivotal, enhancing smart contract functionality and overall system security. Its specialized features make it an indispensable tool for developers navigating the complexities of decentralized applications.
Keywords: blockchain; Bitcoin; Ethereum; Solidity; decentralization